2017
DOI: 10.1159/000480213
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular HSP70 Activates ERK1/2, NF-kB and Pro-Inflammatory Gene Transcription Through Binding with RAGE in A549 Human Lung Cancer Cells

Abstract: Background/Aims: Heat shock protein 70 (HSP70) has been recently described with extracellular actions, where it is actively released in inflammatory conditions. Acting as DAMPs (damage associated molecular pattern), extracellular HSP70 (eHSP70) interacts with membrane receptors and activates inflammatory pathways. At this context, the receptor for advanced glycation endproducts (RAGE) emerges as a possible candidate for interaction with eHSP70. RAGE is a pattern-recognition receptor and its expression is incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 54 publications
4
50
0
1
Order By: Relevance
“…JNK and p38 inhibitors exhibited a significant antagonistic effect with rhHsp70, and although they did not significantly reduce IL-1 secretion compared to rhHsp70 alone, this may indicate the role of JNK and p38 signalling pathways in the synthesis of this cytokine. These results are consistent with previous literature that showed that eHsp70 can activate MAPK and NF-B signalling pathways depending on the cell type (Somensi et al, 2017;Zhe et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…JNK and p38 inhibitors exhibited a significant antagonistic effect with rhHsp70, and although they did not significantly reduce IL-1 secretion compared to rhHsp70 alone, this may indicate the role of JNK and p38 signalling pathways in the synthesis of this cytokine. These results are consistent with previous literature that showed that eHsp70 can activate MAPK and NF-B signalling pathways depending on the cell type (Somensi et al, 2017;Zhe et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…The effect of extracellular Hsp70 is mediated through cell surface receptors such as c‐type lectin receptors, scavenger receptors and pattern recognition receptors for advanced glycation end products (RAGE) as well as TLR2 and TLR4. It was demonstrated that eHsp70 can stimulate the production of pro‐inflammatory cytokines through activation of NF‐κB and MAPKs pathways when acting as TLR2/4 receptors agonist . Furthermore, signalling cascades triggered by various TLRs are known to interfere with each other, and cross‐talk between different signalling pathways activated by DAMPs or PAMPs may represent a regulatory mechanism that can control a potentially harmful immune response .…”
Section: Discussionmentioning
confidence: 99%
“…While intracellular Hsp70 exerts a powerful protective and anti‐inflammatory effect, extracellular Hsp70 (eHsp70) is considered as one of the DAMPs and therefore might be able to activate innate and inflammatory responses . eHsp70 can stimulate a pro‐inflammatory effect through binding to several receptors, most notably TLR2 and TLR4, followed by activation of mitogen‐activated protein kinases (MAPKs) and/or nuclear factor κB (NF‐κB) signal transduction pathways, resulting in cytokine production …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among many signaling molecules, Mitogen-activated protein kinases (MAPKs) are early responders to insufficient oxygen. They are made up of four well-described subgroups, i.e.,the extracellular signal-regulated kinases-1 and -2 (ERK1/2), the c-Jun N-terminal kinases (JNK), p38 MAPKs, and extracellular signal-regulated kinase-5 (ERK5/BMK1) [4-6]. In general, ERK1/2 is relevant to cell proliferation/survival, while p38 is associated with cell apoptosis [7-13].…”
Section: Introductionmentioning
confidence: 99%